1999
DOI: 10.1002/(sici)1522-2594(199903)41:3<544::aid-mrm17>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive determination of coronary blood flow velocity with magnetic resonance imaging: Comparison of breath-hold and navigator techniques with intravascular ultrasound

Abstract: The aim of this study was to evaluate two different magnetic resonance (MR) techniques for the noninvasive assessment of intracoronary blood flow. Coronary blood flow velocities were measured invasively in 26 angiographically normal segments of 12 patients. Noninvasive measurements were performed in identical segments with two MR techniques using a 1.5 T MR tomograph (ACS NT, Philips). A single breath‐hold technique (temporal resolution: 140 msec) and a similar non‐breath‐hold technique with prospective naviga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 28 publications
(13 reference statements)
3
20
0
Order By: Relevance
“…L-NMMA profoundly blocked the normal coronary vasomotor response in only 25 segments in 10 subjects such that it was difficult to justify additional studies, especially with L-NMMA, a nonapproved agent. MRI measures of coronary area (16) and CFV (11,18) were validated in prior studies, and our results are comparable with those reported using invasive techniques (2,15,24). Although systemic L-NMMA infusion caused a slight decrease in heart rate and increase in mean arterial pressure possibly mediated by neurohormonal mechanisms (26), the changes in RPP with IHE stress were not different during the placebo and L-NMMA IHE stress sessions.…”
Section: Limitationssupporting
confidence: 83%
“…L-NMMA profoundly blocked the normal coronary vasomotor response in only 25 segments in 10 subjects such that it was difficult to justify additional studies, especially with L-NMMA, a nonapproved agent. MRI measures of coronary area (16) and CFV (11,18) were validated in prior studies, and our results are comparable with those reported using invasive techniques (2,15,24). Although systemic L-NMMA infusion caused a slight decrease in heart rate and increase in mean arterial pressure possibly mediated by neurohormonal mechanisms (26), the changes in RPP with IHE stress were not different during the placebo and L-NMMA IHE stress sessions.…”
Section: Limitationssupporting
confidence: 83%
“…Scout scans were performed to determine the 3D course and orientation of the proximal right coronary artery (RCA). Baseline coronary velocity measurements were obtained using a VCG triggered breath-hold (11-23 sec) velocityencoded spiral cine sequence perpendicular to the RCA (FOV = 250 × 250 mm 2 , matrix = 312 × 312, spatial resolution = 0.8 × 0.8 × 8 mm 3 , TR = 34 ms, TE = 3.5 ms, RF excitation angle = 20°, spiral acquisition window = 27 ms, spiral interleaves = 11, VENC = 35 cm/s). After baseline imaging, each subject performed isometric handgrip for 3.5 min at 30% of their maximum grip strength on a nonmagnetic, handgrip dynamometer [6].…”
Section: Methodsmentioning
confidence: 99%
“…In response to endothelialdependent stressors, changes in coronary artery cross-sectional area and flow velocity occur which are typically assessed by invasive methods. Magnetic resonance flow mapping is non-invasive and validated for endothelialindependent stressors in humans by comparison with Doppler guidewire measurements [2,3]. One prior study [4], performed at 1.5 T and recording 7-11 cine frames per cardiac cycle, assessed coronary flow velocity during isometric handgrip exercise, a well-established provocateur of endothelial-dependent vasoreactivity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance (MR)- [54] and intravascular ultrasound (IVUS)- [55] based techniques have been described to provide valuable diagnostic and anatomical information; however, their temporal and spatial resolution is usually not sufficient for deriving information based on the differentiated velocity vector field such as the wall shear stress distribution [56]. CFD techniques, on the other hand, can provide a significantly larger amount of information on coronary flow dynamics, with greater spatial and temporal resolution, noninvasively, on a patient-specific basis and within a completely virtual environment.…”
Section: Biomedical Implicationmentioning
confidence: 99%